2023
DOI: 10.1128/spectrum.02839-22
|View full text |Cite
|
Sign up to set email alerts
|

Landscape of Exhausted T Cells in Tuberculosis Revealed by Single-Cell Sequencing

Abstract: Identifying the changes in immune cells in response to infection can provide a better understanding of the effects of Mycobacterium tuberculosis on the host immune system. We performed single-cell RNA-sequencing analysis of CD4 + T and CD8 + T cells isolated from peripheral blood mononuclear cells of healthy individuals and patients with tuberculosis to reveal the cellular characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…This subset exhibited a strong inflammatory response, energy metabolism and IFN response. However, many studies have shown ( 61 63 ) that T-cell exhaustion manifests as a result of inactivated T-cell proliferation, the secretion of suppressor cytokines and decreased production of IFNγ.…”
Section: Discussionmentioning
confidence: 99%
“…This subset exhibited a strong inflammatory response, energy metabolism and IFN response. However, many studies have shown ( 61 63 ) that T-cell exhaustion manifests as a result of inactivated T-cell proliferation, the secretion of suppressor cytokines and decreased production of IFNγ.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the normal number of T cells was not equal to normal functions. The research found that chronic infections by viruses and bacteria led the continuous exposure to antigens, causing the overexpression of inhibitory receptors, such as PD-1 [28,29] , CTLA-4 [30] , Tim-3 [31] , and Lag-3 [32] on the surface of CD4 T cells and CD8 T cells, which could reduce the Page 13/16 release of cytokines by T cells and impair the functions of T cells [33] . The phenomenon was called T cell exhaustion, which was associated with the severity of PTB [31,32] .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, active pulmonary TB patients also exhibit T cell exhaustion and dysfunction under sustained MTB antigen stimulation, characterized by reduced production of MTB-specific INF-γ, TNF-α, and IL-2 by CD4 + and CD8 + T cells, as well as increased expression of PD-1 and its ligands on T cells, monocytes, macrophages, and B cells [ 70 ]. Recently, Pan et al [ 71 ] identified 12 genes through single-cell sequencing that may be associated with exhaustion of CD4 + and CD8 + T cells following Mycobacterium infection, including RPS26 , ITM2C , GZMK , IL32 , HLA-DRB1 , TNFAIP3 , JUN , ZFP36L2 , GTF3C1 , ZFP36 , MT2A , and HOPX . Among the features of T cell exhaustion and dysfunction caused by chronic MTB infection, immune checkpoints have gained increasing attention.…”
Section: Immunological Mechanisms Of Ltbimentioning
confidence: 99%